The paradox of obesity with normal weight; a cross-sectional study - Lahav, Yair; Kfir, Aviv; Gepner, Yftach (Frontiers in Nutrition, 2023)
Objective To evaluate the prevalence of excessive adiposity among normal-weight individuals, and their cardiometabolic risk. Methods This cross-sectional study included 3,001 participants (ages 20–95, 52% men, BMI 28.0 ± 5.5 kg/m2) who completed an anthropometric evaluation, dual x-ray absorptiometry (DXA) scan to measure body composition, and cardiometabolic blood markers. Excess adiposity was defined as ≥25% for men and ≥ 35% for women. Results Of the entire study participants, 967 were in normal BMI (18.5–24.9 kg/m2) with a wide body fat distribution (4–49%). Of them, 26% of men and 38% of women were classified with excess adiposity. As compared to normal-weight lean participants, normal-weight obese men and women had higher triglycerides (76.5 ± 37.3 vs. 101.2 ± 50.3 mg/dL, p = 0.004 and 84 ± 44.2 vs. 101.4 ± 91.1 mg/dL, p = 0.030; respectively) and elevated low-density lipoprotein cholesterol (103.3 ± 31.7 vs. 119.6 ± 45.5 mg/dL, p = 0.011) and total cholesterol (171.5 ± 40.3 vs. 190.2 ± 39 mg/dL, p = 0.007) for men only. Among NWO, abdominal circumference was prevalent in 60% of the females with NWO (≥88 cm), but only in 4% of males (≥102 cm). Conclusion Higher adiposity, even within normal weight, increases cardiometabolic risk, and abdominal waist circumference misclassified obesity in normal-weight individuals. This study highlights the need for a body composition evaluation to determine cardiometabolic risk for adults with normal body weight.